1992
DOI: 10.1007/bf00177579
|View full text |Cite
|
Sign up to set email alerts
|

Cellular sequence of tracheal repair in sheep after smoke inhalation injury

Abstract: The cellular repair process of injured tracheal epithelium is described for sheep after exposure to toxic smoke containing high concentrations of acrolein. Fourteen fasted 3-4-year-old ewes had a portion of their cervical trachea exposed to cotton smoke for 20 min and then were sacrificed at various time intervals ranging from 1 to 22 days after exposure. Within 1 day of injury, columnar epithelium sloughed intact from the trachea with a concomitant reduction of nearly 35% in the basal cell population. At 2 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…In previous studies on smokeinduced tracheal injury, we found that in many large areas columnar cells had sloughed off, leaving the basal lamina covered only by a single layer of flattened basal cells [3]. The lamina propria of the tracheal mucosa showed marked congestion and edema with numerous inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies on smokeinduced tracheal injury, we found that in many large areas columnar cells had sloughed off, leaving the basal lamina covered only by a single layer of flattened basal cells [3]. The lamina propria of the tracheal mucosa showed marked congestion and edema with numerous inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in edema formation in the injured tracheal segment was also noted, as evidence by a five to sevenfold elevation in lymphatic drainage, hyperemia, and a significant increase in wet-to-dry weight ratios [1]. The repair of the injured site is characterized initially by proliferation of surviving cells [3,6,10]. Some are nonciliated columnar cells at the edge of the injured area that spread inward and begin to proliferate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations